Effects and safety of aspirin use in patients after cerebrovascular bypass procedures. Issue 4 (26th May 2021) - Lu, Junlin; Shi, Guangchao; Zhao, Yuanli; Wang, Rong; Zhang, Dong; Chen, Xiaolin; Wang, Hao; Zhao, Ji Zong
Abstract : Object: Superficial temporal artery to middle cerebral artery (STA-MCA) bypass is the most effective treatment for Moyamoya disease (MMD). In this study, we aimed to assess whether aspirin improves STA-MCA bypass patency and is safe in patients with MMD. Methods: We performed a retrospective medical record review of patients with ischaemic-onset MMD who had undergone STA-MCA bypass at two hospitals between January 2011 and August 2018, to clarify the effects and safety of aspirin following STA-MCA bypass. The neurological status at the last follow-up (FU) was compared between patients with FU bypass patency and occlusion. Results Among 217 identified patients (238 hemispheres), the mean age was 41.4±10.2 years, and 51.8% were male; the indications for STA-MCA bypass were stroke (48.2%), followed by a transient ischaemic attack (44.0%). Immediate bypass patency was confirmed in all cases. During the FU period (1.5±1.5 y), 15 cases were occluded at FU imaging, resulting in an overall cumulative patency rate of 94%. The patency rates were 93% and 94% in the short-term FU group (n=131, mean FU time 0.5±0.2 years) and long-term FU group (n=107, mean FU time 4.1±3.5 years), respectively. The STA-MCA bypass patency rate in the aspirin group was higher than that in the non-aspirin group (98.7% vs 89.7%; HR 1.57; 95% CI 1.106 to 2.235; p=0.012). No significant difference in the FU haemorrhagic events was observed between the aspirin and non-aspirin groups. Conclusions: Among adult patients with ischaemic-onset MMD undergoing STA-MCA bypass procedures, aspirin might increase the bypass patency rate, without increasing the bleeding risk. FU bypass patency may be associated with a better outcome. Additional studies, especially carefully designed prospective studies, are needed to address the role of aspirin after bypass procedures.